Iron-based nanocrystalline soft magnetic composite material and preparation method thereof

Through the preparation method of multi-stage heat treatment and atomization, the problems of insulating layer decomposition and nanocrystal coarsing of iron-based nanocrystal soft magnetic composite materials under high temperature and long-term heat treatment are solved, and the refinement of nanocrystals and composite properties are realized. Improvement.

CN119419028APending Publication Date: 2025-02-11TIZ ADVANCED ALLOY TECH CO LTD

Patent Information

Application Number
CN202411508569.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the prior art, when preparing iron-based nanocrystal soft magnetic composite materials, high temperature and long-term heat treatment will lead to decomposition of the insulating layer and coarse nanocrystals, which will not fully release the internal stress of the composite material and affect performance.

Method used

Multi-stage heat treatment method using low-temperature destressing heat treatment, medium-temperature nucleation heat treatment and high-temperature short-term crystalline nucleation heat treatment, combined with atomization method to prepare iron-based amorphous magnetic powder, and obtain iron-based soft magnetic composite green body through cold pressing .

Benefits of technology

Fine nanocrystals are precipitated in the amorphous matrix of magnetic powder, reducing the aging and decomposition failure of the insulating layer, fully releasing the internal stress of the composite material, and obtaining iron-based nanocrystal soft magnetic composite materials with high magnetic permeability and low loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419028A_ABST
    Figure CN119419028A_ABST
Patent Text Reader

Abstract

The invention provides an iron-based nanocrystalline soft magnetic composite material and a preparation method, and the iron-based nanocrystalline soft magnetic composite material is prepared by sequentially carrying out low-temperature destressing heat treatment, medium-temperature nucleation heat treatment and high-temperature crystal nucleus growth heat treatment on an iron-based soft magnetic composite material green body, the iron-based soft magnetic composite material green body is prepared by mixing iron-based amorphous magnetic powder, an insulating material and an organic binder and carrying out cold pressing, and the iron-based amorphous magnetic powder is Fe-based amorphous alloy containing Cu. The method has the advantages that through a multi-stage heat treatment mode, fine nanocrystalline can be separated out in an amorphous matrix of magnetic powder, aging decomposition failure of an insulating layer can be reduced, meanwhile, internal stress of the composite material can be fully released, and therefore the iron-based nanocrystalline soft magnetic composite material high in magnetic conductivity and low in loss can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The invention relates to the field of magnetic functional materials, and in particular to an iron-based nanocrystalline soft magnetic composite material and a preparation method thereof. [Background technology]

[0002] Soft magnetic composite materials are a kind of composite materials formed by mixing soft magnetic alloy powder and insulating medium. On the basis of maintaining the original excellent soft magnetic properties of soft magnetic alloy, the resistivity is further improved and the loss is reduced by adding insulating medium. It is one of the core materials for modern electronic technology and industrial applications. Soft magnetic composite materials are usually divided into many types according to the different types of alloys. Among them, iron-based nanocrystalline alloys have high magnetic permeability and high saturation magnetic induction intensity (B s ), low coercivity (H c ) and low raw material cost, which are superior to traditional soft magnetic materials (such as Fe-Si alloys, ferrites, etc.), and have become the key development target of soft magnetic alloys in recent years.

[0003] Nanocrystalline soft magnetic composite materials are more complicated in terms of process than traditional soft magnetic composite materials. It is necessary to prepare the corresponding amorphous matrix powder first, and then heat treat it at a certain temperature, precipitate α-Fe in the amorphous matrix to obtain nanocrystalline powder; after further mixing with the insulating material, additional internal stress will be introduced during the pressing process, and stress relief heat treatment is required again. For example, the Chinese invention patent application with publication number CN117711732A discloses a high-quality factor amorphous nanocrystalline soft magnetic powder core and its preparation method. The process combines the nanocrystallization heat treatment of magnetic powder with the stress relief heat treatment of magnetic ring for a simple process flow, and heat treats for a long time (1 to 3 hours) at the crystallization temperature, while crystallizing and stress relief the composite material. However, the crystallization temperature is high (greater than 500°C), and long-term high-temperature heat treatment will cause the resin used as the insulating binder to decompose, thereby affecting the coating effect; on the other hand, a long heat treatment time will cause the nanocrystals to coarsen, which is not conducive to obtaining low coercivity. If the heat treatment temperature is lowered, the crystallization temperature of the nanocrystals cannot be reached and the nanophase cannot be precipitated; if the heat treatment time is shortened, the composite material cannot be fully stress-relieved and the performance is deteriorated.

[0004] Therefore, there is an urgent need to provide a new process that can precipitate fine nanocrystals in the amorphous matrix of magnetic powder while simplifying the process, reduce the decomposition failure of the insulating layer, and fully release the internal stress of the composite material. [Summary of the invention]

[0005] The technical problem to be solved by the present invention is to provide an iron-based nanocrystalline soft magnetic composite material and a preparation method, which can not only precipitate fine nanocrystals in the amorphous matrix of magnetic powder, but also reduce the decomposition failure of the insulating layer, and at the same time fully release the internal stress of the composite material.

[0006] The present invention is achieved in that:

[0007] In a first aspect, an iron-based nanocrystalline soft magnetic composite material is provided, wherein the iron-based nanocrystalline soft magnetic composite material is obtained by sequentially subjecting an iron-based soft magnetic composite material green body to a low-temperature stress relief heat treatment, a medium-temperature nucleation heat treatment and a high-temperature nucleus growth heat treatment, wherein the iron-based soft magnetic composite material green body is obtained by mixing iron-based amorphous magnetic powder, an insulating material and an organic binder and cold pressing, and the iron-based amorphous magnetic powder is a Fe-based amorphous alloy containing Cu.

[0008] Furthermore, the composition of the iron-based amorphous magnetic powder is any one of FeSiBCu, FeSiBPCu, FeSiBNbCu, FeSiBPNbCu, FeSiBPCCu, and FeSibBPCNbCu, or a mixture of several of them.

[0009] Furthermore, the iron-based amorphous magnetic powder is prepared by an atomization method, which is any one of gas atomization, high-temperature gas atomization, water atomization, water-gas combined atomization, and rotary water atomization, and the powder particle size of the iron-based amorphous magnetic powder is 1 to 50 μm.

[0010] Furthermore, the insulating material is any one of phosphate, silicon oxide, titanium oxide, aluminum oxide, and magnesium oxide, or a mixture of several of them, and the content of the insulating material is 0.1wt.% to 3wt.% of the weight of the iron-based amorphous magnetic powder.

[0011] Furthermore, the organic binder is any one of epoxy resin, silicone resin, epoxy-modified silicone resin, and phenolic resin, or a mixture of the two or more thereof, and the content of the organic binder is 1 wt.% to 5 wt.% of the weight of the iron-based amorphous magnetic powder.

[0012] In a second aspect, a method for preparing an iron-based nanocrystalline soft magnetic composite material comprises the following steps:

[0013] Step 1: preparing iron-based amorphous magnetic powder by an atomization method, mixing the iron-based amorphous magnetic powder, insulating material and an organic binder, and obtaining an iron-based soft magnetic composite material green body by cold pressing;

[0014] Step 2, placing the iron-based soft magnetic composite material green body in an annealing furnace, and introducing a protective gas into the annealing furnace;

[0015] Step 3, raising the temperature of the annealing furnace to a preset low-temperature stress relief heat treatment temperature and keeping the temperature;

[0016] Step 4: Raise the temperature of the annealing furnace to a preset medium-temperature nucleation heat treatment temperature and keep it warm;

[0017] Step 5, raising the temperature of the annealing furnace to a preset high temperature crystal nucleus growth heat treatment temperature and keeping the temperature;

[0018] Step 6: Allow the iron-based nanocrystalline soft magnetic composite material obtained after the heat treatment to cool down along with the annealing furnace, then remove the iron-based nanocrystalline soft magnetic composite material from the annealing furnace and naturally cool it to room temperature.

[0019] Furthermore, in step 3, the low-temperature stress relief heat treatment temperature is 150-350° C., and the heat preservation time is 1-10 hours.

[0020] Furthermore, in step 4, the medium-temperature nucleation heat treatment temperature is 350-500° C., and the holding time is 10-60 minutes.

[0021] Furthermore, in step 5, the high temperature nucleus growth heat treatment temperature is 400-600° C., and the heat preservation time is 10-30 minutes.

[0022] Furthermore, in step 6, the iron-based nanocrystalline soft magnetic composite material is cooled to 150-200° C. along with the annealing furnace.

[0023] By adopting the technical solution of the present invention, at least the following beneficial effects are achieved:

[0024] 1. The iron-based soft magnetic composite material green body is subjected to a multi-stage heat treatment method in which the green body is subjected to a low-temperature long-term stress relief heat treatment, a medium-temperature nucleation heat treatment and a high-temperature short-term crystal nucleus growth heat treatment in sequence. This can not only precipitate fine nanocrystals in the amorphous matrix of the magnetic powder, but also reduce the aging and decomposition failure of the insulating layer. At the same time, it can fully release the internal stress of the composite material, thereby obtaining an iron-based nanocrystalline soft magnetic composite material with high magnetic permeability and low loss.

[0025] 2. The entire preparation process uses the same annealing furnace for heat treatment, and there is no need to take and put materials many times, so the preparation process is very simple.

Brief Description of the Drawings

[0026] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.

[0027] Figure 1 It is a schematic diagram of a multi-stage heat treatment process of the iron-based nanocrystalline soft magnetic composite material of the present invention;

[0028] Figure 2 It is the magnetic permeability detection diagram of Example 1 and Comparative Example 1 in the present invention;

[0029] Figure 3 It is a loss detection diagram of Example 1 and Comparative Example 1 in the present invention. [Specific implementation method]

[0030] In order to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0031] It should be noted that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing these embodiments and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. In addition, the terms "first", "second", etc., etc. are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, features defined as "first", "second", etc. may explicitly or implicitly include one or more of the features.

[0032] See also Figure 1 As shown, the present invention provides an iron-based nanocrystalline soft magnetic composite material, wherein the iron-based nanocrystalline soft magnetic composite material is prepared by sequentially subjecting an iron-based soft magnetic composite material green body to low-temperature stress relief heat treatment, medium-temperature nucleation heat treatment and high-temperature crystal nucleus growth heat treatment, wherein the iron-based soft magnetic composite material green body is obtained by mixing iron-based amorphous magnetic powder, insulating material and organic binder and cold pressing, and the iron-based amorphous magnetic powder is a Fe-based amorphous alloy containing Cu. Since the solid solubility of Cu in Fe is very low in the Fe-based nanocrystalline system containing Cu, Cu clusters will occur preferentially before α-Fe nucleation, and then promote the nucleation of α-Fe as the nucleation site of α-Fe. According to the classical nucleation theory, when the heat treatment temperature is within the nucleation temperature range of α-Fe, the supersaturation of the heat-treated solute atoms is larger at a lower temperature, so the nucleation driving force is large and nucleation is more likely to occur. In addition, the atomic diffusion rate is slow at low temperatures, and the nucleation is not easy to grow, which is conducive to the refinement of nanocrystals. In the present invention, low-temperature and long-term stress relief heat treatment can effectively remove the internal stress of the composite material, medium-temperature nucleation heat treatment can introduce a large number of Cu clusters and promote the nucleation of α-Fe, and high-temperature and short-term nucleus growth heat treatment can further precipitate α-Fe while reducing the decomposition failure of the organic insulating layer.

[0033] In some embodiments of the present invention, the composition of the iron-based amorphous magnetic powder is any one of FeSiBCu, FeSiBPCu, FeSiBNbCu, FeSiBPNbCu, FeSiBPCCu, and FeSibBPCNbCu, or a mixture of several of them.

[0034] In some embodiments of the present invention, the iron-based amorphous magnetic powder is prepared by an atomization method, and the atomization method is any one of gas atomization, high-temperature gas atomization, water atomization, water-gas combined atomization, and rotary water atomization, and the powder particle size of the iron-based amorphous magnetic powder is 1 to 50 μm. In the specific implementation of the present invention, the iron-based amorphous magnetic powder prepared by the atomization method has a spherical structure, and the iron-based soft magnetic composite material green body obtained by cold pressing has a ring-shaped structure.

[0035] In some embodiments of the present invention, the insulating material is any one of phosphate, silicon oxide, titanium oxide, aluminum oxide, and magnesium oxide, or a mixture of several of them, and the content of the insulating material is 0.1wt.% to 3wt.% of the weight of the iron-based amorphous magnetic powder.

[0036] In some embodiments of the present invention, the organic binder is any one of epoxy resin, silicone resin, epoxy-modified silicone resin, and phenolic resin, or a mixture of the two or more thereof, and the content of the organic binder is 1 wt.% to 5 wt.% of the weight of the iron-based amorphous magnetic powder.

[0037] The present invention provides a method for preparing an iron-based nanocrystalline soft magnetic composite material, the preparation method comprising the following steps:

[0038] Step 1, preparing iron-based amorphous magnetic powder by an atomization method, wherein the prepared iron-based amorphous magnetic powder has a spherical structure, mixing the iron-based amorphous magnetic powder, an insulating material and an organic binder, specifically mixing the iron-based amorphous magnetic powder, the insulating material and the organic binder in a required proportion, and cold pressing to obtain an iron-based soft magnetic composite material green body, wherein the iron-based soft magnetic composite material green body has a ring-shaped structure;

[0039] Step 2, placing the iron-based soft magnetic composite material green body in an annealing furnace, and introducing a protective gas into the annealing furnace; in the specific implementation of the present invention, the iron-based soft magnetic composite material green body can be placed on a material tray, and the material tray and the iron-based soft magnetic composite material green body are placed in the annealing furnace together;

[0040] Step 3, raising the temperature of the annealing furnace to a preset low-temperature stress relief heat treatment temperature and keeping the temperature;

[0041] Step 4: Raise the temperature of the annealing furnace to a preset medium-temperature nucleation heat treatment temperature and keep it warm;

[0042] Step 5, raising the temperature of the annealing furnace to a preset high temperature crystal nucleus growth heat treatment temperature and keeping the temperature;

[0043] Step 6: Allow the iron-based nanocrystalline soft magnetic composite material obtained after the heat treatment to cool down along with the annealing furnace, then remove the iron-based nanocrystalline soft magnetic composite material from the annealing furnace and naturally cool it to room temperature.

[0044] In some embodiments of the present invention, in step 3, the low-temperature stress relief heat treatment temperature is 150-350°C, and the holding time is 1-10 hours. In the specific implementation, the temperature of the stress relief heat treatment should not be higher than the decomposition failure temperature of the organic binder, otherwise the excessively high stress relief heat treatment temperature will cause a large amount of decomposition of the resin material, thereby reducing the insulation effect and affecting the overall performance; therefore, the present invention adopts a low temperature of 150-350°C to perform stress relief heat treatment on the green body of the iron-based soft magnetic composite material, and the holding time reaches 1-10 hours, that is, a low temperature and long-term stress relief heat treatment is adopted, which can effectively remove the internal stress of the composite material and prevent the decomposition failure of the organic binder.

[0045] In some embodiments of the present invention, in step 4, the medium temperature nucleation heat treatment temperature is 350-500°C, and the holding time is 10-60 minutes. Since the solid solubility of Cu in Fe is very low in the Cu-containing Fe-based nanocrystal system, Cu clusters will occur preferentially before the nucleation of α-Fe, and then promote the nucleation of α-Fe as the nucleation site of α-Fe; according to the classical nucleation theory, when the heat treatment temperature is within the nucleation temperature range of α-Fe, the supersaturation of the heat-treated solute atoms is greater at a lower temperature, so the nucleation driving force is large and nucleation is more likely to occur. In addition, the atomic diffusion rate is slow at low temperatures, and the nucleation is not easy to grow, which is conducive to the refinement of nanocrystals; therefore, the present invention controls the nucleation temperature at a relatively low temperature of 350-500°C to facilitate the refinement of nanocrystals.

[0046] In some embodiments of the present invention, in step 5, the high temperature crystal nucleus growth heat treatment temperature is 400-600°C, and the holding time is 10-30 minutes. In the process of using the high temperature crystal nucleus growth heat treatment temperature for treatment, it can not only promote the growth of primary crystal nuclei, but also further promote the nucleation and precipitation of more α-Fe. At the same time, in order to reduce the decomposition and failure of the organic binder at high temperature, the present invention controls the holding time within a short time of 10-30 minutes, that is, a high temperature and short time crystal nucleus growth heat treatment is used to effectively reduce the aging, decomposition and failure of the organic binder (organic insulating layer).

[0047] In some embodiments of the present invention, in step 6, the iron-based nanocrystalline soft magnetic composite material is cooled to 150-200° C. together with the annealing furnace, so as to remove the iron-based nanocrystalline soft magnetic composite material.

[0048] By adopting the above technical solution of the present invention, at least the following beneficial effects are achieved:

[0049] 1. The iron-based soft magnetic composite material green body is subjected to a multi-stage heat treatment method in which the green body is subjected to a low-temperature long-term stress relief heat treatment, a medium-temperature nucleation heat treatment and a high-temperature short-term crystal nucleus growth heat treatment in sequence. This can not only precipitate fine nanocrystals in the amorphous matrix of the magnetic powder, but also reduce the aging and decomposition failure of the insulating layer. At the same time, it can fully release the internal stress of the composite material, thereby obtaining an iron-based nanocrystalline soft magnetic composite material with high magnetic permeability and low loss.

[0050] 2. The entire preparation process uses the same annealing furnace for heat treatment, and there is no need to take and put materials many times, so the preparation process is very simple.

[0051] The technical solution of the present invention is further described in detail below through some specific embodiments and comparative examples:

[0052] Example 1

[0053] Will contain Fe 73.5 Si 13.5 B 9 Nb 3 Cu 1 The green body of the amorphous magnetic powder, 0.5wt% phosphating layer and 2wt% epoxy resin amorphous / nanocrystalline soft magnetic composite material is placed on a material tray, and the material tray and the composite material are pushed into the annealing furnace together and the protective gas is introduced. The temperature of the annealing furnace is raised to the preset low-temperature stress relief heat treatment temperature of 200°C and kept warm for 5 hours; then, the temperature of the annealing furnace is raised to the preset medium-temperature nucleation heat treatment temperature of 420°C and kept warm for 30 minutes; then, the temperature of the annealing furnace is raised to the preset high-temperature crystal nucleus growth heat treatment temperature of 550°C and kept warm for 15 minutes; then, the heating power is turned off, so that the iron-based nanocrystalline soft magnetic composite material is cooled to 180°C together with the annealing furnace, and then removed from the annealing furnace and naturally cooled to room temperature.

[0054] Example 2

[0055] Will contain Fe 73.5 Si 13.5 B 9 Nb 3 Cu 1 Amorphous magnetic powder and 0.5wt% SiO 2The insulating layer and the amorphous / nanocrystalline soft magnetic composite green body of 2wt% organic silicone resin are placed on the material tray, and the material tray and the composite material are pushed into the annealing furnace together and the protective gas is introduced. The temperature of the annealing furnace is raised to the preset low-temperature stress relief heat treatment temperature of 300°C and kept warm for 3 hours; then, the temperature of the annealing furnace is raised to the preset medium-temperature nucleation heat treatment temperature of 420°C and kept warm for 60 minutes; then, the temperature of the annealing furnace is raised to the preset high-temperature crystal nucleus growth heat treatment temperature of 550°C and kept warm for 15 minutes; then, the heating power is turned off, so that the iron-based nanocrystalline soft magnetic composite material is cooled to 180°C together with the annealing furnace, and then removed from the annealing furnace and naturally cooled to room temperature.

[0056] Example 3

[0057] Will contain Fe 80.5 Si 6 B 12 Cu 1.5 The green body of the amorphous magnetic powder, 0.5wt% phosphating layer and 2wt% epoxy resin amorphous / nanocrystalline soft magnetic composite material is placed on a material tray, and the material tray and the composite material are pushed into the annealing furnace together and the protective gas is introduced. The temperature of the annealing furnace is raised to the preset low-temperature stress relief heat treatment temperature of 200°C and kept warm for 5 hours; then, the temperature of the annealing furnace is raised to the preset medium-temperature nucleation heat treatment temperature of 360°C and kept warm for 30 minutes; then, the temperature of the annealing furnace is raised to the preset high-temperature crystal nucleus growth heat treatment temperature of 480°C and kept warm for 15 minutes; then, the heating power is turned off, so that the iron-based nanocrystalline soft magnetic composite material is cooled to 180°C together with the annealing furnace, and then removed from the annealing furnace and naturally cooled to room temperature.

[0058] Comparative Example 1

[0059] The amorphous / nanocrystalline soft magnetic composite green body used is the same as that in Example 1, which is placed on a material tray, and then the material tray and the composite material are pushed into an annealing furnace together and a protective gas is introduced. The temperature of the annealing furnace is raised to 550°C and kept warm for 60 minutes; then, the heating power is turned off, and the iron-based nanocrystalline soft magnetic composite material is cooled to 180°C together with the annealing furnace, and then removed from the annealing furnace and naturally cooled to room temperature.

[0060] Comparative Example 2

[0061] The amorphous / nanocrystalline soft magnetic composite green body used is the same as that in Example 2, which is placed on a material tray, and then the material tray and the composite material are pushed into an annealing furnace together and a protective gas is introduced. The temperature of the annealing furnace is raised to 550°C and kept warm for 60 minutes; then, the heating power is turned off, and the iron-based nanocrystalline soft magnetic composite material is cooled to 180°C together with the annealing furnace, and then removed from the annealing furnace and naturally cooled to room temperature.

[0062] Comparative Example 3

[0063] The amorphous / nanocrystalline soft magnetic composite green body used is the same as that in Example 3, which is placed on a material tray, and then the material tray and the composite material are pushed into an annealing furnace together and a protective gas is introduced. The temperature of the annealing furnace is raised to 480°C and kept warm for 60 minutes; then, the heating power is turned off, and the iron-based nanocrystalline soft magnetic composite material is cooled to 180°C together with the annealing furnace, and then removed from the annealing furnace and naturally cooled to room temperature.

[0064] Testing: The magnetic properties of the iron-based nanocrystalline soft magnetic composite materials prepared in the above Examples 1-3 and Comparative Examples 1-3 were measured;

[0065] The effective magnetic permeability μ of the sample at 100kHz is measured by a broadband LCR tester. e And the magnetic permeability under bias magnetic field; and the power analyzer was used to measure the sample at f = 100kHz, B m =Total loss at 100mT. Figure 2 Shown are the magnetic permeability detection diagrams of Example 1 and Comparative Example 1, Figure 3 Shown are loss detection diagrams of Example 1 and Comparative Example 1.

[0066] The specific test results are shown in the following table:

[0067]

[0068] From the above table and Figure 2 , Figure 3 As shown, the iron-based nanocrystalline soft magnetic composite material prepared by the multi-stage heat treatment method of the present invention can improve the overall magnetic permeability and resistivity of the composite material, reduce power loss, and at the same time improve the magnetic permeability under a bias magnetic field, making it more suitable for use in high-frequency devices.

[0069] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.

Claims

1. An iron-based nanocrystalline soft magnetic composite material, characterized in that: The iron-based nanocrystalline soft magnetic composite material is prepared by subjecting an iron-based soft magnetic composite material green body to low-temperature stress relief heat treatment, medium-temperature nucleation heat treatment and high-temperature crystal nucleus growth heat treatment in sequence, wherein the iron-based soft magnetic composite material green body is mixed with iron-based amorphous magnetic powder, insulating material and organic binder and obtained by cold pressing, and the iron-based amorphous magnetic powder is a Fe-based amorphous alloy containing Cu.

2. The iron-based nanocrystalline soft magnetic composite material according to claim 1, characterized in that: The iron-based amorphous magnetic powder is composed of any one of FeSiBCu, FeSiBPCu, FeSiBNbCu, FeSiBPNbCu, FeSiBPCCu, and FeSibBPCNbCu, or a mixture of several of them.

3. The iron-based nanocrystalline soft magnetic composite material according to claim 1, characterized in that: The iron-based amorphous magnetic powder is prepared by an atomization method, wherein the atomization method is any one of gas atomization, high-temperature gas atomization, water atomization, water-gas combined atomization, and rotary water atomization, and the powder particle size of the iron-based amorphous magnetic powder is 1 to 50 μm.

4. The iron-based nanocrystalline soft magnetic composite material according to claim 1, characterized in that: The insulating material is any one of phosphate, silicon oxide, titanium oxide, aluminum oxide, and magnesium oxide, or a mixture of the two or more thereof, and the content of the insulating material is 0.1 wt.% to 3 wt.% of the weight of the iron-based amorphous magnetic powder.

5. The iron-based nanocrystalline soft magnetic composite material according to claim 1, characterized in that: The organic binder is any one of epoxy resin, silicone resin, epoxy-modified silicone resin and phenolic resin or a mixture of the two or more thereof, and the content of the organic binder is 1 wt.% to 5 wt.% of the weight of the iron-based amorphous magnetic powder.

6. A method for preparing the iron-based nanocrystalline soft magnetic composite material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Step 1: preparing iron-based amorphous magnetic powder by an atomization method, mixing the iron-based amorphous magnetic powder, insulating material and an organic binder, and obtaining an iron-based soft magnetic composite material green body by cold pressing; Step 2, placing the iron-based soft magnetic composite material green body in an annealing furnace, and introducing a protective gas into the annealing furnace; Step 3, raising the temperature of the annealing furnace to a preset low-temperature stress relief heat treatment temperature and keeping the temperature; Step 4: Raise the temperature of the annealing furnace to a preset medium-temperature nucleation heat treatment temperature and keep it warm; Step 5, raising the temperature of the annealing furnace to a preset high temperature crystal nucleus growth heat treatment temperature and keeping the temperature; Step 6: Allow the iron-based nanocrystalline soft magnetic composite material obtained after the heat treatment to cool down along with the annealing furnace, then remove the iron-based nanocrystalline soft magnetic composite material from the annealing furnace and naturally cool it to room temperature.

7. The method for preparing an iron-based nanocrystalline soft magnetic composite material according to claim 6, characterized in that: In step 3, the low-temperature stress relief heat treatment temperature is 150-350° C., and the heat preservation time is 1-10 hours.

8. The method for preparing an iron-based nanocrystalline soft magnetic composite material according to claim 6, characterized in that: In step 4, the medium temperature nucleation heat treatment temperature is 350-500° C., and the holding time is 10-60 minutes.

9. The method for preparing an iron-based nanocrystalline soft magnetic composite material according to claim 6, characterized in that: In step 5, the high temperature nucleus growth heat treatment temperature is 400-600° C., and the heat preservation time is 10-30 minutes.

10. The method for preparing an iron-based nanocrystalline soft magnetic composite material according to claim 6, characterized in that: In step 6, the iron-based nanocrystalline soft magnetic composite material is cooled to 150-200° C. along with the annealing furnace.

Citation Information

Patent Citations

  • High-quality-factor amorphous nanocrystalline soft magnetic powder core and preparation method thereof

    CN117711732A

Cited By

  • Laminated soft magnetic composite material and preparation method thereof

    CN122201979A

  • Microcrystalline soft magnetic composite material and method for producing the same

    CN122868296A